Glyphosate resistance in amaranthus viridis in brazilian citrus orchards - Alcántara-De la Cruz, Ricardo; Amaral, Gabriel da Silva; de Oliveira, Guilherme Moraes; Rufino, Luiz Renato; de Azevedo, Fernando Alves; de Carvalho, Leonardo Bianco [UNESP]; da Silva, Maria Fátima Das Graças Fernandes (MDPI, 2020)
Glyphosate is the main tool for weed management in Brazilian citrus orchards, where weeds, such as Conyza bonariensis and Digitaria insularis, have been found with resistance to this herbicide. Field prospections have allowed the identification of a possible new case of glyphosate resistance. In this work, the susceptibility levels to glyphosate on three Amaranthus viridis L. populations, with suspected resistance (R1, R2, and R-IAC), collected in citrus orchards from the São Paulo State, Brazil, as well as their accumulation rates of shikimic acid, were determined. The fresh weight of the susceptible population (S) was reduced by 50% (GR50) with ~30 g ea ha−1 glyphosate, while the GR50 values of the R populations were between 5.4 and 11.3 times higher than that for S population. The LD50 (herbicide dose to kill 50% of individuals of a weed population) values of the S population were ≤150 g ea ha−1 glyphosate, while the LD50 of the R populations ranged from 600 to 920 g ea ha−1 . Based on the reduction of fresh weight and the survival rate, the R1 population showed the highest level of glyphosate resistance, which had GR50 and LD50 values of 248 and 918 g ea ha−1 glyphosate, respectively. The S population accumulated 240 µg shikimic acid at 1000 µM glyphosate, while the R1, R2, and R-IAC populations accumulated only 16, 43, and 33 µg shikimic acid, respectively (between 5.6 to 15 times less than the S population). Enzyme activity assays suggested that at least one target site-type mechanism was involved in resistance. This result revealed the first report of glyphosate resistance in A. viridis reported in the world.
Keywords: Dose-response; Enzyme activity; Herbicide resistance; Shikimic acid; Slender amaranth